Merocyanine‐Benzothiazole Chromophore‐Based Sensor for Selective Picric Acid Detection. Issue 34 (9th September 2019) - Patil, Pramod D. Jawale; Wagalgave, Sopan M.; Ingle, Rajita D.; Nanubolu, Jagadeesh B.; Bhosale, Rajesh S.; Bhosale, Sidhanath V.; Pawar, Rajendra P.; Bhosale, Sheshanath V.
Abstract: We report synthesis of (2E, 4E)‐2‐(benzo[d]thiazol‐2‐yl)‐4‐(1, 3, 3‐trim ethylindolin‐2‐ylidene) but‐2‐enenitrile (MC‐BTH‐1) chromophore and employed for picric acid sensing. MC‐BTH‐1 was prepared by Knoevenagel condensation of 2‐(benzo[d]thiazol‐2‐yl) acetonitrile and (Z)‐2‐(1, 3, 3‐trimethylindolin‐2‐ylidene)acetaldehyde in the presence of catalytic amount of piperidine in dry ethanol. The MC‐BTH‐1 conjugate displayed a remarkable sensing property towards picric acid in presence of interfering nitroaromatic compounds. The sensing of nitroaromatic compounds was investigated by means of UV‐vis absorption, fluorescence and 1 H NMR spectroscopic. Furthermore, colorimetric visualization of receptor MC‐BTH‐1 with the addition of various analytes under 365 nm UV light shows only color change from green to dark green for 2, 4, 6‐trinitrophenol (TNP) and no significant color change was observed for other analytes. Under optimized condition the detection limit towards TNP and 2, 4‐dinitrophenol (DNP) are 1.58×10 −9 M and 1.48×10 −9 M, respectively. These results clearly show high sensitivity of system at low concentration with fluorescence quenching quantum efficiency ∼88%. Abstract : We report synthesis of MC‐BTH‐1 receptor and employed for detection of various nitroaromatic analytes. Among them, receptor shown to be very selective for picric acid and even in the presence of interfering nitroaromatic compounds. The receptor shows detection limit towards TNP and 2, 4‐dinitrophenol (DNP) are 1.58×10 −9 M and 1.48×10 −9 M, respectively.